TMS activation of interhemispheric pathways between the posterior parietal cortex and the contralateral motor cortex. - Koch, G; Ruge, D; Cheeran, B; Fernandez Del Olmo, M; Pecchioli, C; Marconi, B; Versace, V; Lo Gerfo, E; Torriero, S; Oliveri, M; Caltagirone, C; Rothwell, J (2009)
Using a twin coil transcranial magnetic stimulation (tc-TMS) approach we have previously demonstrated that facilitation may be detected in the primary motor cortex (M1) following stimulation over the ipsilateral caudal intraparietal sulcus (cIPS). Here we tested the interhemispheric interactions between the IPS and the contralateral motor cortex (M1). We found that conditioning the right cIPS facilitated contralateral M1 when the conditioning stimulus had an intensity of 90% resting motor threshold (RMT) but not at 70% or 110% RMT. Facilitation was maximal when the interstimulus interval (ISI) between cIPS and M1 was 6 or 12 ms. These facilitatory effects were mediated by interactions with specific groups of interneurons in the contralateral M1. In fact, short intracortical inhibition (SICI) was reduced following cIPS stimulation. Moreover, additional comparison of facilitation of responses evoked by anterior-posterior versus posterior-anterior stimulation of M1 suggested that facilitation was more effective on early I1/I2 circuits than on I3 circuits. In contrast to these effects, stimulation of anterior IPS (aIPS) at 90% RMT induced inhibition, instead of facilitation, of contralateral M1 at ISIs of 10-12 ms. Finally, we found similar facilitation between left cIPS and right M1 although the conditioning stimuli had to have a higher intensity compared with stimulation of right cIPS (110% instead of 90% RMT). These findings demonstrate that different subregions of the posterior parietal cortex (PPC) in humans exert both facilitatory and inhibitory effects towards the contralateral primary motor cortex. These corticocortical projections could contribute to a variety of motor tasks such as bilateral manual coordination, movement planning in space and grasping.